The resolution of customary community land rights issues based on government regulation no. 18 of 2021 and its relevance to the constitution in indonesia - Aprido, Rizki; Fatimah, Fatimah (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This research aims to find a solution to the issue of customary community land rights concerning the usurpation of customary land rights in the Percut Sei Tuan District, Deli Serdang Regency. The purpose of this research is to determine the direction of Government Regulation No. 18 of 2021 in shaping policies regarding the resolution of customary land rights of indigenous communities. The research method used in this study is a normative juridical approach conducted by examining secondary data, both primary legal materials (primary sources) and secondary legal materials (secondary sources). The primary legal materials used consist of regulations related to the issues under investigation. The research approach used by the author in this paper is a qualitative approach to examine the problem formulations present in this paper. The nature of the research used by the author is normative research that tests the topic in this paper. The research findings indicate that the orbit of Government Regulation No. 18 of 2021 in shaping policies for resolving disputes regarding the customary land rights occupied by PTPN II. PTPN II is considered not in line with and deviates from the applicable laws, given that the actions of PTPN II have obstructed the indigenous communities from realizing their livelihoods based on their customary land rights. Various efforts have been made to curb the encroachment on customary land in Percut Sei Tuan, but their activities continue due to protection from certain law enforcement authorities, preventing the people of Percut Sei Tuan from benefiting from their customary land rights.